Implementasi Sistem Penggajian Pegawai Berbasis Website Di Restoran Mbledeq - Muhammad Fatchur Rozy; Henny Dwi Bhakti (Jurnal Teknik Informatika dan Teknologi Informasi, 2023)
Technology is very embedded in our lives and our daily activities. The development of this technology makes many jobs easier. This technology can also solve many problems, one of which is business problems. The solution to the problems at the Mbledeq Restaurant can be overcome by creating a Website-Based Payroll System, which includes calculating employee salaries according to attendance, inputting employee data, and reporting employee pay slips. Building a web-based application system that can be used to meet the needs of Mbledeq Restaurant employees, this website-based website is expected to help the Admin process Mbledeq Restaurant payroll data and display details of salary slips received during one month of work. The method used in this research is Rapid Application Development (RAD ). RAD is considered very suitable for this research because it is known to be fast in developing information systems. The method in this research consists of requirements planning, system design, and implementation. By considering the design, implementation, and objectives of creating an employee salary information system at MbledeQ Cafe&Resto Gresik, it can be concluded that building an employee salary information system at MbledeQ Cafe&Resto Gresik so that the employee salary information system becomes a comfortable place for employees to find their pay slips. The salary information system generates attendance reports, salaries & pay slips, which can be given to future employees and also makes it easier for admins to calculate employee salaries.